Analisis Perubahan pH Limbah Air Pencucian Plat setelah Pengujian Jar Test dengan Menggunakan Koagulan Tawas - Priyadi Yahya; Rachmah Nanda Kartika; Yoga Putra Pratama (Pusat riset dan Inovasi Nasional, 2025)
The impacts of wastewater (liquid waste) include contamination and pollution of surface water and other water bodies utilized by humans, as well as disruption to aquatic life. Wastewater generated from plate washing processes in offset printing industries contains toxic substances that can harm the environment, such as ink pigments, additives, alcohol, and other hazardous chemicals. This study aims to reduce the environmental impact caused by plate washing wastewater. The method used in this research is the Jar Test, which is commonly applied to evaluate the effectiveness of coagulants in water and wastewater treatment. Based on the findings, this method successfully reduced the Total Dissolved Solids (TDS) level by 18%. These results indicate that the use of alum as a coagulant has a significant effect on altering the chemical composition of the plate washing wastewater, thereby contributing to pollution reduction